Neuropsychology, social cognition and global functioning among bipolar, schizophrenic patients and healthy controls: preliminary data - Caletti, Elisabetta; Paoli, Riccardo Augusto; Fiorentini, Alessio; Cigliobianco, Michela; Zugno, Elisa; Serati, Marta; Orsenigo, Giulia; Grillo, Paolo; Consonni, Dario; Zago, Stefano; Caldiroli, Alice; Prunas, Cecilia; et al. (Frontiers in Human Neuroscience, 2013)
This study aimed to determine the extent of impairment in social and non-social cognitive domains in an ecological context comparing bipolar (BD), schizophrenic (SKZ) patients and healthy controls (HC). The sample was enrolled at the Department of Psychiatry of Policlinico Hospital, University of Milan; it includes stabilized SKZ patients (n = 30), euthymic bipolar patients (n = 18) and HC (n = 18). Patients and controls completed psychiatric assessment rating scales, the Brief Assessment of Cognition in Schizophrenia (BACS) and the Executive and Social Cognition Battery (ESCB) that contains both ecological tests of executive function and social cognition, in order to better detect cognitive deficits in patients with normal results in standard executive batteries. The three groups differed significantly for gender and substance abuse, however, the differences did not influence the results. BD patients showed less impairment on cognitive performance compared to SKZ patients, even in “ecological” tests that mimic real life scenarios. In particular, BD performed better than SKZ in verbal memory (p < 0.0038) and BACS symbol coding (p < 0.0043). Regarding the ESCB tests, in the Hotel task SKZ patients completed significantly less tasks (p < 0.001), showed a greater number of errors in Multiple Errands Test (MET-HV) (p < 0.0248) and a worse performance in Theory of Mind (ToM) tests (p < 0.001 for the Eyes test and Faux pas test). Both patients' groups performed significantly worse than HC. Finally, significant differences were found between the two groups in GAF scores, being greater among BD subjects (p < 0.001). GAF was correlated with BACS and ESCB scores showing the crucial role of cognitive and ecological performances in patients' global functioning.